Exploring HIV risk behavior and sexual/gender identities among transgender women and their sexual partners in Peru using respondent-driven sampling. Issue 9 (2nd September 2022) - Long, Jessica E.; Sanchez, Hugo; Dasgupta, Sayan; Huerta, Leyla; Calderón Garcia, Dania; Lama, Javier R.; Duerr, Ann
ABSTRACT: HIV prevalence is high among transgender women, but little is known about cisgender men who have sex with transgender women (MSTW). The objective of this study was to investigate characteristics and behavior of MSTW compared to transgender women and men who have sex with men (MSM) using a modified respondent-driven sampling design. Seed participants completed a survey and invited up to three sex partners. Forward recruitment continued in waves through the referral of sex partners. Cross-sectional data were assessed using mixed effects models. From February to July 2018, 479 participants in Lima, Peru enrolled ( n = 199 transgender women, n = 196 MSTW, and n = 45 MSM). MSTW behavior and identity differed significantly from that of transgender women and MSM. MSTW primarily identified as bisexual (69%) or heterosexual (15%) and only 6% reported male partners. Insertive condomless anal intercourse was reported by 61% of MSTW; 46% did not know their HIV serostatus. Compared to MSTW without male partners, those with recent male partners were more likely to sell sex (OR 15.7, 95% CI 4.1–60.5), and report condomless receptive anal intercourse (OR 89.0, 95% CI 19.1–414.8). This evidence suggests that MSTW are a distinct population from MSM, and highlights the critical need to include MSTW in HIV research and interventions.